How Healthcare Systems Negatively Impact Environmental Health? The Need for Institutional Commitment to Reduce the Ecological Footprint of Medical Services - Prisco Piscitelli; Stela Karaj; Alessandro Miani; Tassos C. Kyriakides; Enrico Greco; Elena Colicino; Antonio Bray; Fernando Simón; Vasilis Vasiliou; Andrea A. Baccarelli (MDPI AG, 2023)
The global healthcare industry plays a crucial role in preserving human health and well-being [...]